PTH-043 Adult coeliac disease remission assessment:does a D1 biopsy increase the detection of villous atrophy?. (8th June 2018) - Marks, Lauren; Lau, Michelle; Kurien, Matthew; Hadjivassiliou, Marios; Mooney, Peter; Cross, ProfSimon; Sanders, David
Abstract : Introduction: The duodenal bulb (D1) has been shown to be a sensitive site for detecting villous atrophy (VA) in newly diagnosed coeliac disease (CD), however there is a scarcity of data from those with established CD. In patients with established CD, we aim to establish whether D1 biopsies improved the identification of VA compared to biopsies from the second part of the duodenum (D2) alone. Methods: 251 patients with established CD were prospectively recruited from the endoscopy department at the Royal Hallamshire Hospital between 2013 and 2017. These patients were undergoing repeat gastroscopy to assess dietary adherence. All patients underwent a gastroscopy, with one biopsy taken from the duodenal bulb and four from D2. Biopsies were classified according to Marsh criteria. We assessed concordance of histology between the D1 and D2 sites, and 95% confidence intervals were calculated for all results using a binominal distribution. Results: 251 patients were recruited (70.5% female, age range 17–81 years, median age 53 years) having been on a gluten-free diet for a median duration of 6 years. Concordant results: 35.1% (n=88, 95% CI: 29.16 to 40.96) had normal duodenal biopsies in both D1 and D2; 32.3% (n=81, 95% CI: 26.49 to 38.05) had VA in D1 and D2; 18.3% (n=46, 95% CI: 13.54 to 23.11) had raised intra-epithelial lymphocytes (IELs) only in both D1 and D2. Disconcordant results: 4.4% (n=11, 95% CI: 1.85 to 6.91) had VA in D1 but not D2; 2.4% (n=6, 95% CI: 0.50 to 4.28) had raised IELs in D1 but normal histology in D2. 2.8% (n=7, 95% CI: 0.75 to 4.83) had VA in D2 but normal histology in D1; 4.8% (n=12, 95% CI: 2.14 to 7.42) had IELs in D2 but normal histology in D1. Conclusions: VA was confined to the duodenal bulb in 4.4% of patients with established CD. Thus a D1 biopsy in addition to distal duodenal biopsies increases the likelihood of detecting VA, although the significance of isolated VA in the bulb in patients on a gluten-free diet is yet to be determined.